All my friends - Larson, Hope (New York : Farrar Straus Giroux Books for Young Readers, 2021)
When Fancy Pink is offered a record deal their parents say no, so they decide to make an album on their own, if they can raise enough money without raising their parents' suspicions.
Sequel to: All together now.
Ages 9-14.
Grades 4-6.
Keywords: Graphic novels; Musicians -- Fiction; Bands (Music) -- Fiction; Family life -- California, Southern -- Fiction; Dating (Social customs) -- Fiction; Racially mixed people -- Fiction; California, Southern -- Fiction; Graphic novels